Perkembangan Pondok Pesantren Al-Masyhuriyah Masa K.H. Moh Hasan Al Muhtadi Billah - Kamilah, Isfina Muzayyana; Fadlil, Moh Umar (Department of History and Islamic Civilization, Faculty of Adab and Humaniora, UIN Sunan Ampel Surabaya, 2025)
This article discusses the development of the Al-Masyhuriyah Islamic Boarding School in Situbondo, East Java. Developed in 1999 AD, this Islamic boarding school has had a very long process in facing the challenges and developments of the times, especially in the process of establishing a formal school. The involvement of AlMasyhuriyah Islamic boarding school successors and social support from peers are important factors in building a conducive formal school. The Al-Masyhuriyah Islamic Boarding School not only provides access to extensive education, but the students are also taught to manage the land that the chaplain has handed over to his students. Until now, this cottage still follows the traditions of ancient cottages.